Role of carbon monxide in cardiovascular function - Durante, William (John Wiley & Sons, Ltd, 2006)
Carbon monoxide (CO) is an endogenously derived gas formed from the breakdown of heme by the enzyme heme oxygenase. Although long considered an insignificant and potentially toxic waste product of heme catabolism, CO is now recognized as a key signaling molecule that regulates numerous cardiovascular functions. Interestingly, alterations in CO synthesis are associated with many cardiovascular disorders, including atherosclerosis, septic shock, hypertension, metabolic syndrome, and ischemia-reperfusion injury. Significantly, restoration of physiologic CO levels exerts a beneficial effect in many of these settings, suggesting a crucial role for CO in maintaining cardiovascular homeostasis. In this review, we outline the actions of CO in the cardiovascular system and highlight this gas as a potential therapeutic target in treating a multitude of cardiovascular disorders.